The Effect of Capital Expenditure, Local Revenue, and Employee Expenditure on Local Government Financial Performance - Gina Fadilah; Irwan Sutirman Wahdiat (Danadyaksa: Post Modern Economy Journal, 2026)
This research investigates the determinants of Financial Performance in District/City Governments in West Java (2021-2024). Using Institutional Theory and a quantitative approach, the study analyzes 99 observations from audited Budget Realization Reports (LRA). The regression model is highly robust 96.7% is the coefficient of determination (R). The results reveal that Locally-Owned Revenue (PAD) has a positive and significant effect and serves as the primary driver of execution. Conversely, Capital Expenditure and Personnel Expenditure exert significant negative pressure, reflecting fiscal rigidities and high maintenance burdens. While PAD is a component of the autonomy ratio, its positive impact reflects genuine managerial capacity in internalizing decentralization pressures. The study recommends prioritizing PAD digitalization and conducting rigorous spending reviews to enhance fiscal efficiency.